Being Frank - Earnhardt, Donna W. (Flashlight Press, 2012)
Frank struggles to learn the art of being tactful when he observes that his friend has freckles resembling the Big Dipper, his teacher has breath that smells like onions, and his principal's toupee looks like a weasel.